On the lifetime of metastable metallic hydrogen - Burmistrov, S.N.; Dubovskii, L.B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The molecular phase of hydrogen converts to the atomic metallic phase at high pressures estimated usually as 300–500 GPa. We analyze the zero-temperature decay of metallic phase as the pressure is relieved below the transition one. The metallic state is expected to be in the metastable long-lived state down to about 10–20 GPa and decays instantly at the lower pressures. The pressure range of the long-lived metastable state is directly associated with an impossibility to produce a stable hydrogen molecule immersed into the electron liquid of high density. For lower pressures, the nucleation of an electron-free cavity with the energetically favorable hydrogen molecule inside cannot be suppressed with the low ambient pressure.